A 3D conductive network of porous carbon nanoparticles interconnected with carbon nanotubes as the sulfur host for long cycle life lithium–sulfur batteries. Issue 47 (27th November 2018) - Luo, Shiqiang; Sun, Weiwei; Ke, Jianhuang; Wang, Yiqi; Liu, Shuangke; Hong, Xiaobin; Li, Yujie; Chen, Yufang; Xie, Wei; Zheng, Chunman
Abstract : We report the design of a novel 3D conductive network structure (CNTs/Co–NC) and its application as a sulfur host for Li–S batteries. Abstract : Constructing an interlinked three-dimensional conductive carbon structure as a sulfur host is considered to be an effective strategy for suppressing the capacity decay over long-term cycling and improving the rate performance of lithium–sulfur (Li–S) batteries, because it can not only facilitate rapid electronic and ionic transportation in the cathode, but also be conducive to confine lithium polysulfide (LiPS) dissolution and shuttling. In this report, we designed a novel 3D conductive network structure (CNTs/Co–NC), which is composed of Co–NC (cobalt embedded in an N-doped porous carbon composite) derived from ZIF-67 polyhedra and inserted carbon nanotubes (CNTs), and applied it as a sulfur host for Li–S batteries. The CNT/Co–NC network structure is firstly prepared via the in situ nucleation of small ZIF-67 crystals on the surface of CNTs and eventually grown into CNT/ZIF-67 hybrid materials; after subsequent carbonization and infiltration of sulfur procedures, the S@CNT/Co–NC cathode is obtained. Li–S batteries based on the S@CNT/Co–NC cathode show an improved rate capability of 772.6 mA h g −1 at the 2 C rate, enhanced long cycling stability under a large current density with a low capacity decay rate of ∼0.067% per cycle at the 0.5 C rate after 500 cycles and ∼0.072% per cycle at the 1 C rate after 700 cycles and an excellent coulombic efficiency of about 95% up to 500 cycles at 0.5 C and 91% up to 700 cycles at 1 C. The superior performance of S@CNTs/Co–NC should be ascribed to the rapid charge transfer, excellent electron conductivity, improved adsorption capability for LiPSs and enhanced redox kinetics of this 3D conductive network structure.